The role of lex2 in lipopolysaccharide biosynthesis in Haemophilus influenzae strains RM7004 and RM153 - Griffin, R.; Cox, Andrew D.; Makepeace, Katherine; Richards, James C.; Moxon, E. Richard; Hood, Derek W. (Society for General Microbiology, 2003)
The locus lex2, comprising lex2A and lex2B, contributes to the phase-variable expression of lipopolysaccharide (LPS) of Haemophilus influenzae and was found to be present in 74 % of strains investigated. lex2A contains 59-GCAA repeats which vary in number from 4 to 46 copies between strains. The locus was cloned from the serotype b strains RM7004 and RM153 and showed >99 % nucleotide sequence identity between these strains and the published lex2 sequence. Disruption of the lex2B gene in strain RM7004 resulted in truncation of some LPS glycoforms, shown by gel fractionation, with only one glycoform reacting with a digalactosidespecific monoclonal antibody, 4C4, compared with four LPS glycoforms in the more elongated LPS of the parent strain. Mass spectrometry and NMR analyses of LPS from the lex2B mutant revealed loss of the terminal digalactoside as well as the second b-glucose extending from the first heptose of the inner core. The authors conclude that Lex2B is the b-(1-4)-glucosyltransferase that adds the second b-glucose to the first b-glucose as part of the oligosaccharide extension from the first heptose of the LPS of strain RM7004. Investigation of the expression of the lex2 locus indicated that the genes are co-transcribed and that both reading frames are required for addition of this second b-glucose in a phase-variable manner.